A MORAL CONDEMNATION OF SAME SEX MARRIAGE AS A BREACH OF NATURAL LAW DOCTRINE - Akpa, Matthew Ikechukwu (EBSU Journal of Social Sciences and Humanities, 2023)
In human relation and marital relationship, it has been from time in memorial that the conjugal fusion should be between people of opposite gender and any modernity against this is a breach of natural doctrine. The law of nature has prescribed the modus of doing things and any move away from this law is naturally condemnable. This is the major problem with same sex marriage or homosexuality. The agitators of this version of marriage states that it is permissible for a man to marry a man or a woman to marry another woman. However, the researcher discovered that this agitations and permutation does not have any natural backup and it’s also against some cultural doctrines and laws of certain groups and societies. The researcher therefore recommended that the practice of gay marriage and all sorts of homosexual relationship should be stopped forthwith as such is against nature and nurture because any further agitation or persuasion might aggravate the lot of the supreme being against the creatures.